Rancang Bangun Aplikasi PHP dalam Mendeteksi Penyakit Kelinci Menggunakan Metode Case-Based Reasoning (CBR) - Fithry Tahel; Siti Aliyah; Muhammad Adam (Journal of Computer System and Informatics (JoSYC), 2020)
The case-based reasoning method is one of the methods for building a system with the decision-making of a new case based on solutions from previous cases. This method provides a space on experts in giving similar or similarity value to the revealed knowledge. The disease in rabbit animals often makes the owner confused by the lack of owner knowledge about the animal's disease. Most of the diseases that occur in the pet rabbit are often underestimated, and if the disease is not immediately treated it will become more severe and serious in handling. Therefore, it is necessary a tool or a system that has a doctor's ability to diagnose diseases. The system is an expert system that seeks to adopt human knowledge to the computer in order to solve problems such as those commonly done by experts. The results showed that the case-based reasoning method can be used as a way to diagnose the type of disease suffered in rabbits